URGENSI INOVASI PENGELOLAAN KEUANGAN, SARANA DAN PRASARANA DALAM PENDIDIKAN - Maharani, Tyara; Ismail, Fajri; Karoma (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This article aims to discuss the urgency of innovation in financial management, facilities and infrastructure in education. This research uses a qualitative descriptive approach and method, systematic analysis of theories and regulations that are directly related to the title of the research, through a library research method approach. After collecting various books and related journals to discuss, then analyze the material through the study library with the results of the analysis in descriptive form. Management of finances, facilities and infrastructure requires creativity and innovation from educational component institutions in exploring resources, utilizing them according to needs, and carrying out financial bookkeeping that is transparent and can be accounted for in accordance with applicable laws and regulations.